Implementation of Nursing Care for Patient Mrs. I with PID (Pelvic Inflammatory Disease) Post HDLO in Fulfilling Disturbances in Comfort: Pain with Five Finger Hypnotherapy in the Treatment Room on the Second Floor of the Dr. Iman Sudjudi Pavilion, Gatot Soebroto Army Hospital - , M. Kep, Ns.Ita, S. Kep (STIKes RSPAD RSPAD Gatot Soebroto, 2024)
PID (Pelvic Inflammatory Disease) or pelvic inflammatory disease is an inflammation of the female reproductive organs that usually occurs in the uterus, fallopian tubes, and ovaries. This occurs due to bacterial infection in sexually transmitted infections (STIs). The prevalence of PID cases in the world in 2019 was 1.05 million cases in women of childbearing age. In Indonesia in 2020, around 300,000 women with gonorrhea and chlamydia infections caused 24,000 - 46,000 cases of PID in women each year. Based on data from the Treatment Room on the 2nd Floor of the dr. Iman Sudjudi Pavilion, Gatot Soebroto Army Hospital, from November 2023 to April 2024, there were 15 patients out of 803 patients treated. The medical management carried out was surgery which can cause post-operative pain. The purpose of this writing is to be able to understand nursing care for PID patients with post HDLO in Mrs. I with acute pain nursing problems by performing complementary actions, namely five-finger hypnotherapy. This study is a descriptive method with a case study approach for PID (Pelvic Inflammatory Disease) patients post HDLO with acute pain in the Treatment Room on the Second Floor of the dr. Iman Sudjudi Pavilion, Gatot Soebroto Army Hospital. The results of this study indicate that in PID patients with post HDLO with acute pain who underwent complementary actions of five-finger hypnotherapy for 3x24 hours, the results showed a decrease in the intensity of the pain scale, before the pain scale was 6 and after it was done it became a pain scale of 2. The conclusion obtained is that there is an effect of five-finger hypnotherapy on reducing the intensity of the pain scale in PID post HDLO patients. Therefore, this method can be applied as a complementary therapy to reduce pain in post HDLO patients.